Uterine Carcinosarcoma in a Patient with Didelphys Uterus. (7th March 2013) - Iavazzo, C.; Kokka, F.; Sahdev, A.; Singh, N.; Reynolds, K.
Abstract : Background . Didelphys uterus is a noncommon finding in women. Till now, few cases with benign mesenchymal tumors in patients with didelphys uterus are described. We present a case of a patient with carcinosarcoma arising in a didelphys uterus. Case . A 73-year-old patient presented with profuse watery postmenopausal bleeding. On examination under anesthesia, left and right cervixes were identified. Tumor extended from the left cervix into the lower third of the vagina and was adherent to the right vaginal sidewall. There was no evidence of parametrial extension. Tissue was sent for biopsy which revealed high-grade uterine carcinosarcoma. Two uterine fundi and two vaginas in keeping with uterine didelphys were identified on imaging. The patient underwent vaginal excision of the protruding tumor measuring 8 × 6  cm with harmonic scalpel followed by total abdominal hysterectomy and bilateral salpingooophorectomy. Although a number of pelvic and paraaortic lymph nodes were also identified on imaging, she was not planned for lymphadenectomy after MDT (multidisciplinary team) discussion because of her comorbidities. The final histology confirmed the diagnosis. Conclusion . According to our knowledge, this is the second case of carcinosarcoma arising in didelphys uterus in the world literature.